Paediatric Deep Neck Infection-The Risk of Needing Intensive Care - Perina, Vojtech; Szaraz, David; Harazim, Hana; Urik, Milan; Klabusayova, Eva (Children (Basel, Switzerland), 2022)
Deep neck infections are potentially dangerous complications of upper respiratory tract or odontogenic infections. The pathophysiology, clinical presentation, and potential spreading depend on the complex anatomy of the neck fascia. These infections can lead to severe pathological conditions, such as mediastinitis, sepsis, and especially airway impairment with difficult management. Because of the risk of life-threatening emergency situations and the possible impacts on the overall health status of affected children, their early recognition is of utmost importance. Torticollis, drooling, and stridor are the most common signs of advancing disease. Children presenting with these symptoms should be admitted to the paediatric intensive care unit for vital function monitoring, where the airway could be readily secured if function is compromised.
Keywords: complications; deep neck infection; children; anatomy; paediatric; airway management; intensive care